When music and emotions meet machine - Kota, Soumya; Krishna Prasanna, M; Madhusudhan Reddy, D (International Journal of Engineering and Technology, 2018)
Perception about music varies person to person. But, what most of them love listening to, is music. The discussion thatâ€™s exciting is, emotion and cognition go hand in hand in music.Genres like classical, jazz, rock, blues, country, no matter what, people listen, feel and enjoy the essence of it.Surprisingly we can relate music and emotions. Every piece of music is created to convey certain emotions and that is why emotion has been considered a powerful way for accessing music information. Large collection of music is being created and accessed today. To make the userâ€™s choice easier, the (MIR) music informational retrieval community has made an effort to train a machine (like computer) to detect the emotion of a music signal.Making a machine identify the emotion of music leads to better interaction between the machine and the user. It is possible to play the music according to the userâ€™s mood by detecting the psychological or facial cues. Also, this can be used to sort userâ€™s music collection according to their mood with an adjective described. Intensity and quality of musical emotions change overtime.Therefore, various discussions and debates led to research and proposal of data model training and result set according to the userâ€™s emotion. Â Â